2015
DOI: 10.1007/s12041-015-0569-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead pollution on fitness and its dependence on heterozygosity in Drosophila subobscura

Abstract: Lead is one of the most present contaminants in the environment, and different species respond differently to this type of polution. If combined with genomic stress, lead may act synergistically, causing significant decrease of fitness components. We used two genetically diverse Drosophila subobscura populations (regarding both putatively adaptive inversion and microsatellite loci polymorphisms) originating from two ecologically distinct habitats. To establish different levels of genome heterozygosity, series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Life history traits also varied significantly between the populations and kept a similar pattern as microbiota in D. melanogaster on the standard substrate, whereby egg-to-adult viability was higher in the Kalna population compared to Slankamen. D. subobscura did not show significant differences in egg-to-adult viability regarding the origin, nor regarding the substrate composition, as was shown by Tanasković et al [17]. On the other hand, developmental time results revealed that D. subobscura underwent more changes in this trait regarding the microbial composition, population origin and substrate than D. melanogaster.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Life history traits also varied significantly between the populations and kept a similar pattern as microbiota in D. melanogaster on the standard substrate, whereby egg-to-adult viability was higher in the Kalna population compared to Slankamen. D. subobscura did not show significant differences in egg-to-adult viability regarding the origin, nor regarding the substrate composition, as was shown by Tanasković et al [17]. On the other hand, developmental time results revealed that D. subobscura underwent more changes in this trait regarding the microbial composition, population origin and substrate than D. melanogaster.…”
Section: Discussionmentioning
confidence: 48%
“…Lead is one of the widespread heavy metals that has previously been reported to have a major negative impact on Drosophila fitness [15]. However, it has been shown that its negative impact can be modified depending on the population genetic background [16], genome heterozygosity [17] and genetic variation [18]. Since Drosophila species are mainly exposed to lead through food intake, it was suggested that gut microbiota could also have an impact on the species resistance to lead toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Size reduction under stressful lead conditions observed in this study is in concordance with previous results in D. subobscura (KURBALIJA NOVICIC et al, 2012;KENIG et al, 2013) suggesting that lead interferes with finely tuned processes of wing development, causing size reduction. It is interesting to note that although developmental time in examined groups is significantly prolonged (TANASKOVIC et al, 2015), under lead stress wing size is reduced, suggesting possible trade-off between two traits. Each organism has limited amount of available energy that can be directed in life history processes such as viability, development, reproduction, growth and body size and resource allocation in one trait is usually accompanied by reduction of other trait (VAN NOORDWIJK and DE JONG, 1986;STEARNS, 1992;REZNICK et al, 2000;ROFF, 2002).…”
Section: Resultsmentioning
confidence: 96%
“…Heavy metal pollution is regarded as one of the most important environmental stress factor (PACYNA and PACYNA, 2001) mainly caused by anthropogenic activities, with lead being the most widespread pollutant (NRIAGU and PACYNA, 1988). It has been shown that lead prolongs developmental time (COHN et al, 1992;BERZINS and BUNDY, 2002;JEZIERSKA et al, 2009;HUANGA et al, 2014;TANASKOVIC et al, 2015), reduces life span (MASSIE et al, 1992) and even influences complex behavioral traits such as courtship (MASSIE et al, 1992;HIRSCH et al, 2003). Studies show that lead can affect morphological traits, mainly by reducing body size in fish (CANLI and ATLI, 2003), wing size in Drosophila (KURBALIJA NOVIČIĆ et al, 2012), or causing malformation of body structures (VERMEULEN et al, 2000;HAYWOODA et al,2004;SPARLING et al, 2006).…”
mentioning
confidence: 99%